THE EFFECTIVENESS OF USING COOPERATIVE LEARNING IN TEACHING READING COMPREHENSION - Jamia’an, Zainuddin; Jano, Zanariah (Journal of Human Capital Development (JHCD), 2016)
Many Malaysian primary school pupils have problems in understanding English texts that could be impacting their English achievement. This study is to ascertain the effectiveness of using cooperative learning in teaching reading comprehension. The sample comprised fifty-eight year six pupils who were chosen randomly from a population of eighty-seven. T-test results indicated that the experimental group (cooperative learning method) made gains in post-test 1 and post-test 2 for both reading comprehension score and overall English score but not for the control group (direct instruction method). The result of this study reveal that cooperative learning method brings a positive effect on pupil’s reading comprehension ability. This study is beneficial for teachers of English and policy maker of school in incorporating cooperative learning in school system. Future research should gear toward examining teachers and administrators’ perceptions in order to improve the implementation of CL method in school system. Keywords: cooperative learning, reading, comprehension, English